2015
DOI: 10.1158/1940-6207.capr-14-0447
|View full text |Cite
|
Sign up to set email alerts
|

In VivoAntineoplastic Effects of the NSAID Sulindac in an Oral Carcinogenesis Model

Abstract: The antineoplastic properties of the NSAID sulindac have long been studied. The purpose of this study was to explore sulindac's in vivo effects on oral squamous cell carcinoma (SCC) oncogenesis using the hamster cheek pouch oral carcinogenesis model (HOCM). Thirty Syrian golden hamsters were divided into three experimental and two control groups (n ¼ 6 each). The animals' right buccal pouches were treated with carcinogen for 9 weeks in one experimental and one control group and for 14 weeks in all other three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Notably, sulindac, a nonsteroidal anti‐inflammatory drug, inhibits pancreatic carcinogenesis through the inhibition of K‐ras protein prenylation by targeting AKR1B10 . Moreover, sulindac has been shown to inhibit cell proliferation and tumor growth in an oral carcinogenesis model . A recent study showed that AKR1B10 overexpression conferred resistance to cisplatin in A549 cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, sulindac, a nonsteroidal anti‐inflammatory drug, inhibits pancreatic carcinogenesis through the inhibition of K‐ras protein prenylation by targeting AKR1B10 . Moreover, sulindac has been shown to inhibit cell proliferation and tumor growth in an oral carcinogenesis model . A recent study showed that AKR1B10 overexpression conferred resistance to cisplatin in A549 cells .…”
Section: Discussionmentioning
confidence: 99%
“…34 Moreover, sulindac has been shown to inhibit cell proliferation and tumor growth in an oral carcinogenesis model. 35 A recent study showed that AKR1B10 overexpression conferred resistance to cisplatin in A549 cells. 36 Cisplatin resistance reduces survival in patients with advanced stage head and neck SCC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the results of H&E stain and IHC staining utilizing Bcl-2 and Bak antibodies revealed variable observations. The HBP oral carcinogenesis model in the current study was used because is the best known animal system that closely correlates with sequential common events involved in the development of human oral premalignant and malignant lesion (16) .…”
Section: Discussionmentioning
confidence: 99%
“…There are several examples that playing an important role in medicinal and pharmaceutical chemistry [2], including Esomeprazole [7,8], which acts as proton-pump inhibitor; the selective NK 2 antagonist ZD7944 [9]; and the anti-cancer agent Sulindac ® (Figure 1) [10].…”
Section: Introductionmentioning
confidence: 99%
“…There are several examples that playing an important role in medicinal and pharmaceutical chemistry [2], including Esomeprazole [7,8], which acts as proton-pump inhibitor; the selective NK2 antagonist ZD7944 [9]; and the anti-cancer agent Sulindac ® (Figure 1) [10]. Modafinil (also known as Provigil ® [11], Figure 2), another important sulfoxide, is administered as a drug against narcolepsy [12] with significant advantages compared to dexamphetamine [13] and several other stimulants [14] because of a lower abuse potential [15,16].…”
Section: Introductionmentioning
confidence: 99%